(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Nutritional issues among elementary school-aged children remain a public health challenge in Indonesia. Children aged 5–12 are vulnerable to nutritional problems such as stunting, wasting, obesity, and anemia. Data from the Basic Health Research (Riskesdas) (2018) shows the prevalence of stunting at 23.6%, anemia at 26.8%, wasting at 9.2%, and obesity at 20%. In Sumedang Regency, the prevalence of stunting reached 27.6% (SSGI 2017) and remains a major problem. This condition is exacerbated by the consumption of unhealthy snacks around schools, which poses a risk to students’ health. Therefore, early nutrition education and literacy efforts are needed to increase children’s understanding of the importance of healthy eating habits. This community service activity was held face-to-face at Manangga Public Elementary School, South Sumedang District, Sumedang Regency, on September 17, 2025. The target group was all third and fourth-grade students, with approximately 70 participants. The methods used included counseling, discussions, "Isi Piringku" (My Plate) simulations, educational games, and evaluation through pre- and post-tests. The results of the activity showed an increase in students’ knowledge of the Balanced Nutrition Guidelines, from 33% in the pre-test to 69% in the post-test. Students demonstrated high enthusiasm throughout the activity, as evidenced by their active participation in discussions and simulations. Teachers and school officials responded positively and emphasized the importance of continuing the nutrition education program at school. This activity can be concluded as effective in improving the nutritional literacy of elementary school students. It is hoped that students will adopt healthy eating patterns in their daily lives, while schools and parents need to continue promoting balanced nutrition habits to support optimal child growth and development.